English language anxiety and motivation towards speaking english among Malaysian pre-university students - Ramarow, Hasvinii; Che Hassan, Norlizah (Canadian Center of Science and Education, 2021)
This study aims to identify the level of English language anxiety and level of motivation in speaking English among Malaysian Pre-University students. The research sample was composed of pre-university students in Selangor, Malaysia. Using a quantitative research method, the researcher distributed a survey questionnaire which was developed by adapting existing questionnaires by Pappamihiel (2002) for English language anxiety scale and Schmidt, Boraie, and Kassabgy (1996) for motivation. Results of the data analysis established there was a low level of English language anxiety in speaking English among pre-university students, and moderate level of motivation, yet the level of intrinsic motivation was slightly lower than the level of extrinsic motivation in speaking English among pre-university students. The results showed there was a significant correlation between English language anxiety and motivation in speaking language. However, there was no significant difference in gender for English language anxiety and motivation. There was a significant difference on races for English language anxiety and insignificant differences on races for motivation. The findings of this study may serve as a platform for school authorities and policymakers in developing motivation and reducing language anxiety among students.